Dimensionally stable NiFe@Co/Ti nanoporous electrodes by reactive deposition for water electrolysis - Yao, S.; Wang, C.; Li, M.; Cheng, Y.; Xing, W.; Jiang, San Ping (Elsevier Ltd, 2017)
The development of efficient and dimensionally stable electrode plates is of a significant challenge for the oxygen evolution reaction in the industrial water electrolysis process. In this work, structurally stable electrode plates are developed based on the nanostructured Ni-Fe catalysts on highly porous and dimensionally stable Co reactive deposited on Ti substrates, Ni-Fe@Co/Ti. SEM analysis shows the hierarchically structured micro- and nano-porous structure of the Co electrode on Ti substrates by reactive deposition route. The surface area of the reactive deposited Co is 3 times larger than that of the conventional electrodeposited Co electrode, providing highly porous and stable base for the subsequent deposition of Ni-Fe electrocatalysts. The as-prepared Ni-Fe@Co/Ti electrode exhibits high catalytic activity towards oxygen evolution in alkaline solutions, achieving an onset potential of as low as 1.44 V (η = 210 mV) and delivering a current of 10 mA cm−2 at an overpotential of 0.26 V. Most importantly, the electrode shows excellent stability with negligible degradation under the discharge current density at 100 mA cm−2 for 100 h, demonstrating the practical applicability of the Ni-Fe@Co/Ti nanostructured electrodes for industrial scale water electrolysis.